Energy and security in South Asia : cooperation or conflict? - Ebinger, Charles K. (Delhi : Foundation Books, 2011)
"Argues that mistrust, ethnic and religious sectarianism, and political parochialism among the nations of South Asia, a region of strategic geopolitical importance, prevent the region from achieving energy security, which is crucial for economic development and political stability. Recommends measures to improve energy security through domestic policy reform and more effective bilateral and multilateral cooperation"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Power resources -- Asia, South; Energy policy -- Asia, South